A pre-post study of stressors and burnout affecting breast radiologists before and during the COVID-19 pandemic - Jay R. Parikh; Grayson L. Baird; Martha B. Mainiero (European Journal of Radiology Open, 2023)
Rationale and objective: To compare burnout and stressors of breast radiologists prior to and during the COVID-19 pandemic. Materials and methods: Members of the Society of Breast Imaging were emailed an IRB-approved survey in January 2021 during the COVID–19 pandemic. Survey included questions from the Maslach Burnout Inventory and specific stressors including work pace, work-life balance, care of dependents, and financial strain. Data were compared to previous surveys prior to the pandemic. Results: The response rate was 25% (261/1061) for those who opened the email. Of the respondents, 74% (194/261) were female, 82% (214/261) were white, 73% (191/261) were full time, 71% (185/261) were fellowship trained, 41% (106/261) had more than 20 years of experience, and 30% (79/261) were in academic practice.Respondents in 2021 reported frequent levels of depersonalization (2.2) and emotional exhaustion (3.4) while reporting frequent levels of personal accomplishment (5.3), a protective factor. These values were nearly identical before the pandemic in 2020: (2.2, 3.5, 5.3, respectively, p = .9). Respondents rated practicing faster than they would like as the highest stressor; however, 5 of the 6 stressors improved after the pandemic onset (p < .05). Conversely, participants perceived these stresses had gotten slightly worse since the pandemic (p < .01). Almost 50% of respondents reported they were considering leaving their practice; the most common reason was work/life balance. Conclusion: Burnout in breast radiologists remains frequent but unchanged during the COVID-19 pandemic. While participants perceived that some stressors were worse during the pandemic, there was slight improvement in most stressors between the pre-pandemic and pandemic cohorts.